Role of the lateral channel in catalase HPII of Escherichia coli. - Sevinc, M. S. (Cold Spring Harbor Laboratory Press, 1999)
The heme-containing catalase HPII of Escherichia coli consists of a homotetramer in which each subunit contains a core region with the highly conserved catalase tertiary structure, to which are appended N- and C-terminal extensions making it the largest known catalase. HPII does not bind NADPH, a cofactor often found in catalases. In HPII, residues 585-590 of the C-terminal extension protrude into the pocket corresponding to the NADPH binding site in the bovine liver catalase. Despite this difference, residues that define the NADPH pocket in the bovine enzyme appear to be well preserved in HPII. Only two residues that interact ionically with NADPH in the bovine enzyme (Asp212 and His304) differ in HPII (Glu270 and Glu362), but their mutation to the bovine sequence did not promote nucleotide binding. The active-site heme groups are deeply buried inside the molecular structure requiring the movement of substrate and products through long channels. One potential channel is about 30 A in length, approaches the heme active site laterally, and is structurally related to the branched channel associated with the NADPH binding pocket in catalases that bind the dinucleotide. In HPII, the upper branch of this channel is interrupted by the presence of Arg260 ionically bound to Glu270. When Arg260 is replaced by alanine, there is a threefold increase in the catalytic activity of the enzyme. Inhibitors of HPII, including azide, cyanide, various sulfhydryl reagents, and alkylhydroxylamine derivatives, are effective at lower concentration on the Ala260 mutant enzyme compared to the wild-type enzyme. The crystal structure of the Ala260 mutant variant of HPII, determined at 2.3 A resolution, revealed a number of local structural changes resulting in the opening of a second branch in the lateral channel, which appears to be used by inhibitors for access to the active site, either as an inlet channel for substrate or an exhaust channel for reaction products.